Frontier Marshal Based on a Book by Stuart N. Lake - Lake, Stuart N. (Arrow Academy, 2017)
The second of three films based on the Wyatt Earp biography by Stuart N. Lake, "Frontier Marshal" stars Randolph Scott as Marshal Earp of Tombstone. Earp and his brothers enforce the law as much by reputation as by gunplay. Occasionally the marshal's efforts are complicated by his "friendly enemy" Doc Halliday (based on Doc Holliday and played by Cesar Romero), a consumptive gunslinger who runs the gambling activities in town. When a murderous outlaw (Joe Sawyer) invades Tombstone and kills Halliday, Earp is moved to action - and the result is the gunfight at the O.K. Corral. A remake of the 1934 film of the same name, "Frontier Marshal" was itself remade by John Ford as "My Darling Clementine" (1946), with Henry Fonda as Earp and Victor Mature as Doc Holliday. [www.allmovie.com]